Exploring the perceptions of Adolescent’s Black Female Learners in Public School of STEM Careers in terms of its significance towards individual Economic Empowerment: A case study of Bona Comprehensive High School in Soweto, South Africa - Sikhosana, Hope Nosipho (University of the Witwatersrand, Johannesburg, 2023)
Low enrolment of females in Science, Technology, Engineering and Mathematics (STEM) careers is a persistent problem in South Africa and Globally. The issue was greatly exacerbated by the history of gender-based discrimination and oppression, particularly in the workplace and in education. This unequal way of life between men and women of different races was established and maintained in large part by power structures like apartheid and patriarchy. Women have been underrepresented in STEM disciplines as a result of discrimination and sexism. But as the balance of power shifted over the years, many women—and particularly those from historically marginalized groups—were given encouragement to enter STEM areas. However, despite the efforts, women number in STEM remains low. The study investigated how Black adolescent female students in public schools perceived STEM occupations to better understand the low representation of women in STEM fields. The researcher conducted a qualitative case study at Bona Comprehensive School in Soweto to fulfil this goal. A purposive sampling strategy was utilized to choose 1 Life Orientation teacher, while an intentional snowball sampling technique was used to sample 10 Black Adolescent Female students. In-depth one-on-one telephone interviews were performed to collect data, with a semi-structured interview schedule serving as the research tool. Thematic content analysis was used to examine the data that had been gathered. Results show that female students view occupations in medical favourably because they see them as safe and feminine, whereas they view careers in electrical engineering and construction as dangerous and masculine. Also, the results demonstrate that participants' positive perceptions were influenced by the good pay associated with STEM fields because they felt that economic empowerment was crucial to changing their lives and the lives of their families. The lack of resources from the school for hands-on learning, however, was a challenge for the female students as they pursued STEM degrees. In order to keep and attract female students in STEM fields, there is a need to better support them throughout their academic careers. In the research report's latter sections, recommendations are given.
A dissertation on a research study project presented in partial fulfilment of the requirements for the degree Master of Arts (Social Work) by research to the Department of Social Work, School of Human and Community Development, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Economic empowerment; Gender inequality; Gender; Public schools; STEM (Science, Technology, Engineering and Mathematics) careers; Adolescents; UCTD; SDG-4: Quality education; SDG-5: Gender equality